Identification and Gene Mapping of the Lesion Mimic Mutant lm8015-3 - Wang, Chen; Wang, Beifang; Cao, Liyong; Zhang, Yingxin; Gao, Yu; Cao, Yongrun; Zhang, Yue; Liu, Qunen; Zhang, Xiaohui (Frontiers in Sustainable Food Systems, 2022)
Lesion mimic mutants (LMMs) exhibit spots on leaves without fungal infection pressure. The spots confer variable resistance to pathogens in different LMM, making them useful research materials. It is unclear how the rice immune system responds to infection with the fungal pathogen Magnaporthe oryzae (M. oryzae). Here, we identified a rice LMM, lm8015-3, which shows reduced resistance to M. oryzae. We used Quantitative Real-Time PCR (qRT-PCR) to observe the immune system response to M. oryzae–induced lm8015-3. Lm8015-3, obtained from an ethyl methane sulfonate (EMS)–induced Zhonghui8015 (ZH8015) library, showed orange-yellow spots starting in the seedling stage and accumulated more H2O2, resulting in severe degradation of the chloroplast. With map-based cloning, the target gene was located on chromosome 12. Once inoculated with M. oryzae, the expression level of pathogen-related genes of lm8015-3 was downregulated between 48 and 72 h. In addition, more germinating spores appeared in lm8015-3. Therefore, we conclude that M. oryzae weakening the immune system of lm8015-3 from 48 to 72 h makes lm8015-3 more susceptible to M. oryzae. These results suggested that understanding how LMMs defend against M. oryzae infection will contribute to improving rice breeding.